Learn SQL In a Weekend - Dicken, Deanna
With this book as your guide, you can progress from basic database design to the more advanced techniques of database communication in just one weekend. On Friday evening, start with the basics of SQL as you set up a sample database. On Saturday, practice database communications as you cover queries, the SELECT command, and relational database creation. Pull it all together on Sunday with optimization techniques and security triggers. End the weekend with a practical look at how programmers use SQL to make their jobs easier and how popular programming languages can access your database